Key Opinion Leadership in Educational Branding: Ary Ginanjar’s Communication Strategy in Building the Image of Ary Ginanjar University - Suryadi, Doddy; Minasyan, Sona (Economics, Business, Accounting & Society Review, 2026)
In the digital and highly competitive higher education environment, institutional branding increasingly extends beyond conventional marketing toward the strategic use of symbolic figures who embody credibility, values, and legitimacy. While prior studies emphasize social media strategies and organizational accounts, limited attention has been given to founders as Key Opinion Leaders (KOLs) shaping university identity. This study aims to analyze how Key Opinion Leadership operates as a communication strategy in building the image of Ary Ginanjar University (UAG). Employing a qualitative single-case study design, data were collected through in-depth interviews with institutional leaders, communication teams, lecturers, students, alumni, and prospective students, complemented by observations and document analysis. Thematic analysis was used to identify patterns of symbolic leadership, value-based branding, and cross-channel communication alignment. The findings reveal that Ary Ginanjar functions as a brand anchor who transfers personal credibility and value narratives into institutional identity through symbolic leadership, narrative consistency, and integrated digital communication. KOL-based branding not only strengthens public trust and brand awareness but also shapes collective identity within the academic community. The study implies that sustainable university branding requires institutionalizing values beyond individual dependency. Theoretically, this research reframes KOL as a long-term trust architecture in educational branding, offering an actor-centered perspective for higher education reputation management.